Analysis of The Effectiveness of Mathematics On Students MTs Negeri 2 Medan - Nasution, Devi Maia Sari; Palitan, Palitan (JMEA : Journal of Mathematics Education and Application, 2024)
This research discusses the problem of how effective mathematics learning is using a scientific approach at MTs Negeri 2 Medan which was carried out in TP 2023-2024. The aim of this research is to determine the results of the analysis of the effectiveness of mathematics learning using a scientific approach for students at MTs Negeri 2 Medan TP 2023-2024. This research is a descriptive research. Research conducted on 44 MTs 2 Medan students in the field was to analyze the effectiveness of mathematics learning through a scientific approach. This research was conducted in class VII-2 students at MTs Negeri 2 Medan with the subject of transformation. Learning mathematics can be said to be effective by using a scientific approach. This is known from observations of the percentage of student learning recapitulation of 91% which is very active. And seen from each indicator of student activity, the percentage equal to 100% of students plays an active role. From the data obtained there were 3 students who disturbed their friends with a percentage of 5.75%, 16 students did not understand the problem with a percentage of 36.56%, and students understood the problem with the highest number of students, with 25 students and with the highest percentage of 57.69%. So it can be concluded that the average student activity is experienced in the learning process activities, so that there is Effectiveness in Mathematics Learning Using a Scientific Approach for MTs Negeri 2 Medan Students in the 2023/2024 academic year.